ASSOCIATION OF INFORMATION RELATED CONTRACEPTION ON YOUTH’S FUTURE WILLINGNESS IN USING CONTRACEPTIVE METHODS - Andi Angki Fatimah (Proceedings of the International Conference on Applied Science and Health, 2017)
Introduction: One of family planning program objectives for adolescent are informed the youth about some options that they can undertake in terms of controlling their fertility. For instance, married adolescent women in Indonesia were decide to use contraceptive methods when they already had children, and more common on those who has living child Aims: This study aims to examine the association between information related contraception to youth’s willingness to use contraceptive methods Methods: This study used secondary data from Indonesian Demographic and Health Survey (IDHS) 2012, specifically on youth sample in Sulawesi region. There were 2,975 never married youth aged 15 – 24 was analyzed. Univariate and multi variate analysis was performed with occupied binary logistic regression models to measure youth intention on contraceptive methods in the future. Results: Female youth were less likely to be more aware to use contraceptive methods in the future comparing to male youth. Youth with some secondary and higher than secondary education have intention to use contraceptive methods when they have a family, compare with those who has lower than secondary school, and also when they got family planning information from watching television. Furthermore, youth who lived in Central Sulawesi, Gorontalo, and North Sulawesi showed that they want to use contraceptive methods in the future, modern and traditional methods as well. Conclusion: The study result indicate that higher education and better accessibility on family planning information via television give contribution on youth thought in intention to use contraceptive methods in the future when they get married. Besides that, information regarding contraceptive methods should concern with region and custom or culture where youth lived. Knowledge on modern and traditional contraceptive methods also needs to be improved in terms of adding more methods that can be concern in the future for deciding the best methods to choose.